Measuring anxiety and fear of Covid-19 among older people: psychometric properties of anxiety and fear of Covid-19 scale (AMICO) in Spain - Aurora Vélez-Morón; Rafael T. Andújar-Barroso; Regina Allande-Cussó; Juan Jesús García-Iglesias; Gregoria Aquino-Cárdenas; Juan Gómez-Salgado (BMC, 2022)
Abstract Background The elderly population has proven to be a particularly vulnerable group with regard to the effects of the COVID-19 pandemic. The aim of this study was to study the psychometric properties of the Ansiedad y MIedo a Covid-19 scale (AMICO) on a population-based sample of elderly people. Methods A descriptive and psychometric cross-sectional study, based on questionnaires, was carried out. An exploratory and confirmatory factor analysis was performed, as well as a bivariate analysis between the different sociodemographic variables with respect to the total scale score. Results A sample of 720 adults over 65 years of age was obtained, 52.2% of whom were women. The structure of the factor of the scale showed two factors (fear and anxiety) and was confirmed with good fit parameters. The overall reliability of the scale in terms of internal consistency was α = 0.94. Conclusions The AMICO scale is a valid and reliable instrument to measure anxiety and fear of COVID-19 in the Spanish population over 65 years of age. Women and subjects with a partner showed the highest values of fear and anxiety.